To simplify the expression \(8 + 7 \cdot 6 - 3 \cdot 4 + 6 \cdot 7\), we need to use the order of operations (PEMDAS/BODMAS).
-
Multiply and divide first:
- \(7 \cdot 6 = 42\)
- \(3 \cdot 4 = 12\)
- \(6 \cdot 7 = 42\)
Now substitute these values back into the expression:
\[ 8 + 42 - 12 + 42 \]
-
Now, proceed with addition and subtraction from left to right:
- First, calculate \(8 + 42 = 50\)
- Next, calculate \(50 - 12 = 38\)
- Finally, calculate \(38 + 42 = 80\)
Therefore, the simplified result is \(80\).
The correct response is 80.